Inflammatory responses in early pregnancy: Physiological and pathological perspectives - Yasuyuki Negishi; Rimpei Morita (Reproductive Medicine and Biology)
Abstract Background Several conditions such as infertility, repeated implantation failure, and recurrent pregnancy loss can pose challenges in early pregnancy. These issues can be caused by the abnormal inflammatory response with various factors, including exogenous and endogenous agents, and pathogenic and nonpathogenic agents. In addition, they can be exacerbated by maternal immune response to the abovementioned factors. Methods This review aimed to assess the detrimental inflammatory effects of chronic endometritis, endometrial microbiota disturbance, and maternal immune system abnormalities on early pregnancy. Further, essential details such as ovulation, implantation, trophoblast invasion, and placental formation, were examined, thereby highlighting the beneficial roles of inflammation. Main Findings Excessive inflammation was associated with various early pregnancy disorders. Meanwhile, a lack of appropriate inflammation could also contribute to the development of different early pregnancy complications. Conclusion Excessive inflammation and insufficient inflammation can possibly lead to abnormal conditions in early pregnancy, and appropriate inflammation is required for a successful pregnancy.